Effect of Contact Time and Concentration on Adsorption of Pb2+Metal Ion Utilizing Crab Shell Chitosan and Activated Bentonite Clay Composite - Sasria, Nia; Wisaka, Adi; Yusariarta Putra Parmita, Ade Wahyu; Nur Tajalla, Gusti Umindya (UI Scholars Hub, 2025)
Indonesia produced 1,508 tons of nonliving crabs in the January–March 2020 period. The number of shells generated can account for 40%–60% of the overall weight. Therefore, using crab shells made into chitosan is expected to increase the economic value and reduce waste from crab shells. Chitosan can be modified with clay previously activated with an acid solution to form a chitosan–clay composite to improve the adsorption capacity. This study aims to analyze the differences in characteristics between chitosan and clay before and after the immobilization process. A comparison of chitosan and clay (1:2) is conducted on the basis of variations in the contact time for 5, 30, 55, and 80 min and in the concentration of metal solution as much as 10, 30, and 50 ppm. The results of the Fourier transform infrared spectroscopy (FTIR) study found stretching vibrations of –NH originating from the chitosan structure, as well as several functional groups from clay, such as silanol (Si–OH) and siloxane (Si–O–Si). The results of the X-ray diffraction (XRD) test show that the clay used was bentonite clay. Meanwhile, the scanning electron microscopy (SEM) and surface area analyzer (SAA) test results show that the chitosan–clay adsorbent has a rougher and hollower surface with a surface area of 23,666 m2/g. The best adsorption percentage of 90.59% occurred at a concentration of 10 ppm with a contact time of 30 min.